ENGLISH MORPHEME ACQUSITION AS A SECOND LANGUAGE AMONG CHILDREN IN ONLINE GAMING ENVIRONMENTS - Asih Prihandini; Dadang Sudana; Eri Kurniawan (University of Kuningan, 2025)
This study aims to explore the acquisition of English morphemes which is the second language used by children through their interaction in online games. English morphemes, which have different structures from Indonesian morphemes, are analyzed based on their types, especially on root, affixation, stem and base. This study uses a qualitative approach with descriptive analysis. The research sample consists of children aged 7 to 12 years old who have experience playing online games. Observations were made to identify the use of relevant English morphemes. The results show that children can understand and use roots both as content words and function words. However, not all lexical morphemes are found in children's speech, nor are bound roots as part of morphemes. The types of affixes used by children in playing online games are affixes at the beginning and end. There is no use of infixes. Root, stem and base which are word building elements have been used by children in the context of online games.